Functioning model of the GTO testing center Àn the basis of a pedagogical university - L.I. Kostyunina,; S.V. Bogatova,; A.A. Barannikov, (Theory and Practice of Physical Culture, 2023)
Objective of the study was the theoretical and methodological substantiation of the functioning model of the GTO Testing Center on the basis of a pedagogical university (hereinafter referred to as the Center). Methods and structure of the study. Carried out: study of normative and program documents; analysis of scientific and methodological works, empirical material on the activities of the Center; modeling. Results and conclusions. On the basis of the provisions of the system, activity, personality-oriented approaches, a model for the functioning of the GTO Testing Center has been developed; substantiated the multi-level structure and nature of the relationship in the process of organizing the activities of the Center, shows the effectiveness of solving the main tasks of attracting students, various groups of the population to the implementation of the GTO standards, the development of mass physical culture and student sports.